2019
DOI: 10.1016/j.compositesb.2019.107079
|View full text |Cite
|
Sign up to set email alerts
|

How do steel fibers improve the shear capacity of reinforced concrete beams without stirrups?

Abstract: Even though the structural behavior steel fiber reinforced concrete (SFRC) has been extensively researched, structural applications are still limited. One barrier to its implementation is the lack of mechanical models that describe the behaviour of SFRC members failing in shear. This paper reviews the effect of steel fibers on the different mechanisms of shear transfer and combines the observations from the literature regarding the parameters that affect the shear capacity of SFRC.Additionally, a selection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 84 publications
3
70
0
3
Order By: Relevance
“…Comparing experimental results on the shear capacity of SFRC beams without stirrups to the capacity predicted using the expressions from Table 1 shows that predicting the shear capacity of SFRC beams without mild steel shear reinforcement is still difficult [20]. The reason for this difficulty is the complex mechanics of the problem, since, as previously mentioned, the steel fibers affect each of the shear-carrying mechanisms [2].…”
Section: Authors Ref Expressionmentioning
confidence: 91%
See 1 more Smart Citation
“…Comparing experimental results on the shear capacity of SFRC beams without stirrups to the capacity predicted using the expressions from Table 1 shows that predicting the shear capacity of SFRC beams without mild steel shear reinforcement is still difficult [20]. The reason for this difficulty is the complex mechanics of the problem, since, as previously mentioned, the steel fibers affect each of the shear-carrying mechanisms [2].…”
Section: Authors Ref Expressionmentioning
confidence: 91%
“…One failure mode where crack shape and width is essential, is shear failure. When steel fibers are included in the concrete mix, and the reinforced concrete element built with this concrete mix is tested in shear, then the addition of the steel fibers influences all mechanisms that contribute to the shear-carrying capacity of the member [2]. Since the mechanics of the problem are still not fully understood, it is interesting to study the behavior of steel fiber-reinforced concrete (SFRC) with longitudinal steel reinforcement and without shear reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…It is also well known that the initial shear cracking capacity of a RC member is governed by the tensile strength of concrete and, for this reason, any enhancement of the deficient concrete behavior under tension would improve the shear performance of the member. Thus, the effectiveness of non-traditional shear reinforcement such as steel fibers and spirals instead of common steel stirrups has been indicated as a potential alternative technique which provides noticeable improvement of the shear response [1][2][3][4][5]. specimens were bw/h/bf/hf = 150/200/300/50 mm, as shown in Figure 1, whereas the effective depth was equal to d = 175 mm.…”
Section: Introductionmentioning
confidence: 99%
“…However, one of the significant disadvantages of concrete is the weakness of tensile strength and shear resistance. Many studies have been performed to overcome this weakness by focusing on additional components to reinforce concrete [4]. Over the decades, fibers have gained tremendous attention from the research community as a potential improvement to the mechanical properties of concrete [5].…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity analysis results showed that web width, effective depth, and a clear depth ratio were the most important parameters in modeling the shear capacity of steel fiber-reinforced concrete beams.Sustainability 2020, 12, 2709 2 of 34 flexural toughness and tensile strength, the capacity in absorbing energy, ductile behavior, cracking reduction, and improvement of the shear behavior when reinforced [8][9][10]. For this reason, the use of steel fiber-reinforced concrete (SFRC) has become extensively popular in different civil engineering applications such as tunnel shells, concrete sewer pipes, higher upper layers, and slabs of large industrial buildings [4]. Despite many advantages, designing SFRC structures still faces challenges, as it is difficult to determine critical shear capacity by conventional methods [11][12][13].In the literature, various experimental and numerical studies have been performed on SFRC in order to investigate shear strength capacity [10].…”
mentioning
confidence: 99%